Studi Tingkat Efisiensi: Perbandingan Besar Perusahaan dan Efek Krisis Ekonomi - Hakim, Lukmanul (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2012)
The purpose of this study are (I) to analyze the efficiency differences between large andsmall firms. and (2) to analyze the impact of monetary crisis to efficiency, both large andsmall firms_ All the manufacturing firms listed on the JSX are ranked by total assets. The30 highest firms are categorized as the large firms and the 30 lowest firms arecategorized as the small firms. Data taken from the Indonesian Capital Market Directory1999. Six financial ratio are used to represent the company efficiency. Those ratios areconsist of three categories: profitability, liquidity and operation. and leverage. Ingeneral, the result of the study suggest that large and small firms have their ownefficiency niches. There are no differences between large and small firms with regard toefficiency. In addition, consistent with Machfoedz's (1999) study. company efficiency areimpacted by economic crisis. and the large firms are more impacted by economic crisisthan the small one